2021
DOI: 10.1038/s41598-021-89439-2
|View full text |Cite
|
Sign up to set email alerts
|

A human infertility-associated KASH5 variant promotes mitochondrial localization

Abstract: KASH5 is the most recently identified member of the KASH domain family of tail anchored, outer nuclear membrane (ONM) and endoplasmic reticulum (ER) proteins. During meiosis prophase I, KASH5 and SUN1 form a complex that spans the nuclear envelope and which links the telomeres of meiotic chromosomes to cytoplasmic dynein. This connection is essential for homologous chromosome dynamics and pairing. A recent study identified a variant in human KASH5 (L535Q) that correlated with male infertility associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The critical importance of KASH5 during meiosis is exemplified by the KASH5 -/- null mouse, which is completely sterile due to impaired synapsis and resulting meiotic arrest (Horn et al, 2013). Human mutations in the transmembrane domain that cause mistargeting of KASH5 to mitochondria lead to male sterility (Bentebbal et al, 2021). KASH5 shares sequence homology with the N-terminal region of the protein encoded by the zebrafish gene futile cycle which is required for pronuclear migration (Dekens et al, 2003; Lindeman and Pelegri, 2012), another dynein-dependent function in which the female pronucleus uses dynein to migrate towards the male pronucleus along microtubules nucleated from the male centrosome (Gönczy et al, 1999; Payne et al, 2003; Reinsch and Karsenti, 1997; Robinson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The critical importance of KASH5 during meiosis is exemplified by the KASH5 -/- null mouse, which is completely sterile due to impaired synapsis and resulting meiotic arrest (Horn et al, 2013). Human mutations in the transmembrane domain that cause mistargeting of KASH5 to mitochondria lead to male sterility (Bentebbal et al, 2021). KASH5 shares sequence homology with the N-terminal region of the protein encoded by the zebrafish gene futile cycle which is required for pronuclear migration (Dekens et al, 2003; Lindeman and Pelegri, 2012), another dynein-dependent function in which the female pronucleus uses dynein to migrate towards the male pronucleus along microtubules nucleated from the male centrosome (Gönczy et al, 1999; Payne et al, 2003; Reinsch and Karsenti, 1997; Robinson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We posit that the alteration of a single amino acid from a hydrophobic to polar amino acid is able to change the anchoring of mARC1 on the outer mitochondrial membrane and cause its mislocalization, even in the absence of significant protein secondary structure changes ( 43 ). A recent crystal structure study of mARC1 A165T showed that there were alternate conformations of Thr165, even though no difference in protein folding and thermal stability was found between A165T and WT ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…We posit that the alteration of a single amino acid from a hydrophobic to polar amino acid is able to change the anchoring of mARC1 on the outer mitochondrial membrane and cause its mislocalization, even in the absence of significant protein secondary structure changes (41). Our observation that mARC1 A165T is mislocalized to some extent suggests that replacement of Ala by Thr at this position may disrupt mitochondrial anchoring of the protein.…”
Section: Discussionmentioning
confidence: 99%